Post-earthquake Disasters: A Systematic Review of the Classification and Evaluation of the Analysis Methods - Çağatay Takva; Asena Soyluk; Zeynep Yeşim İlerisoy (Geoconservation Research)
Earthquakes are disasters that occur because of tectonic movements under the ground, causing great damage and loss of life. Post-earthquake fires, tsunamis, floods, avalanches, landslides, soil liquefaction, and volcanic eruptions also have devastating effects. Here, we investigate basic analysis methods and specialized methods used for these disasters in academic studies. The study aims to determine and classify the analysis methods developed for post-earthquake disasters that are used in academic studies. Analysis methods are summarized from academic data, classified, and assessed using bibliometric methods. Different analysis methods were used in each post-earthquake disaster and new methods were developed, with a combination of analysis methods in some disasters. There are many academic studies on post-earthquake fires and landslides, and analysis methods have improved. Inadequacy of academic studies on post-earthquake avalanches has been observed.